2013
DOI: 10.4238/2013.november.26.7
|View full text |Cite
|
Sign up to set email alerts
|

Association of the estrogen receptor-β gene RsaI and AluI polymorphisms with human idiopathic thin endometrium

Abstract: ABSTRACT. The aim of this study was to investigate the potential correlation between polymorphisms of the estrogen receptor (ER)-β gene (RsaI and AluI) and ethnic Han Chinese human idiopathic thin endometrium. A total of 120 patients with idiopathic thin endometrium and 120 sterility patients with normal endometrium thickness (controls) were included in the study. RsaI and AluI polymorphisms of the ER-β gene were analyzed with polymerase chain reaction-restriction fragment length polymorphism. The distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…Not only does it occur after uterine cavity manipulation and infection (Shufaro et al, 2008), but it is also related to endocrine disorder, aging, and drug induction (Kumbak and Sahin et al, 2009;Le et al, 2013). The pathological and physiological characteristics of a thin endometrium were first described by Miwa et al (2009) as slow growth of the glandular epithelium, high resistance of the uterine artery blood flow, vascular dysplasia, and low expression of vascular endothelial growth factor (VEGF).…”
Section: Introductionmentioning
confidence: 99%
“…Not only does it occur after uterine cavity manipulation and infection (Shufaro et al, 2008), but it is also related to endocrine disorder, aging, and drug induction (Kumbak and Sahin et al, 2009;Le et al, 2013). The pathological and physiological characteristics of a thin endometrium were first described by Miwa et al (2009) as slow growth of the glandular epithelium, high resistance of the uterine artery blood flow, vascular dysplasia, and low expression of vascular endothelial growth factor (VEGF).…”
Section: Introductionmentioning
confidence: 99%
“…Causes of a "thin" endometrium include damage to the basal layer of the endometrium, hypoestrogenic conditions, prolonged use of oral contraceptives, stimulation of ovulation with clomiphene citrate, radiation therapy [53][54][55], impaired estrogen signaling due to estrogen receptor dysfunction (Erα-and β-polymorphisms) [56,57], while in some cases, the causes remain unknown.…”
Section: "Thin" Endometriummentioning
confidence: 99%
“…Proposed causes of a thin endometrium include Asherman's syndrome and previous intrauterine surgery including sharp curettage, radiation to the pelvis, genetics, impaired uterine blood flow, and acute or chronic endometrial infection. Moreover, it is linked to the use of medications such as clomiphene citrate as well as low estrogen levels or impaired estrogen signaling as a result of dysfunctional estrogen receptors [7][8][9][10][11]. A recent single-cell RNA sequencing study suggested that cellular senescence in the stroma and epithelium together with collagen overdeposition around the blood vessel is involved in endometrial thinness [12].…”
Section: Introductionmentioning
confidence: 99%